Differential Biodistribution of Adenoviral-Vectored Vaccine Following Intranasal and Endotracheal Deliveries Leads to Different Immune Outcomes - Jeyanathan, Vidthiya; Afkhami, Sam; D’Agostino, Michael R.; Zganiacz, Anna; Feng, Xueya; Miller, Matthew S.; Jeyanathan, Mangalakumari; Thompson, Michael R.; Xing, Zhou (Frontiers in Immunology, 2022)
Infectious diseases of the respiratory tract are one of the top causes of global morbidity and mortality with lower respiratory tract infections being the fourth leading cause of death. The respiratory mucosal (RM) route of vaccine delivery represents a promising strategy against respiratory infections. Although both intranasal and inhaled aerosol methods have been established for human application, there is a considerable knowledge gap in the relationship of vaccine biodistribution to immune efficacy in the lung. Here, by using a murine model and an adenovirus-vectored model vaccine, we have compared the intranasal and endotracheal delivery methods in their biodistribution, immunogenicity and protective efficacy. We find that compared to intranasal delivery, the deepened and widened biodistribution in the lung following endotracheal delivery is associated with much improved vaccine-mediated immunogenicity and protection against the target pathogen. Our findings thus support further development of inhaled aerosol delivery of vaccines over intranasal delivery for human application.